2014
DOI: 10.5713/ajas.2013.13373
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of <italic>Butyrivibrio</italic> Group Bacteria in the Rumen of Goats and Its Response to the Supplementation of Garlic Oil

Abstract: This study aimed to investigate the diversity of the Butyrivibrio group bacteria in goat rumen and its response to garlic oil (GO) supplementation as revealed by molecular analysis of cloned 16S rRNA genes. Six wethers fitted with ruminal fistulas were assigned to two groups for a cross-over design with 28-d experimental period and 14-d interval. Goats were fed a basal diet without (control) or with GO ruminal infusion (0.8 g/d). Ruminal contents were used for DNA extraction collected before morning feeding on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 31 publications
2
9
0
Order By: Relevance
“…Our results demonstrated that R. flavefaciens was the most abundant species in the gastrointestinal tract. This result supports the previous finding that R. flavefaciens dominated in the rumen of goats [21]. However, the abundances of R. bromii and F. succinogenes were different in different ruminant species.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results demonstrated that R. flavefaciens was the most abundant species in the gastrointestinal tract. This result supports the previous finding that R. flavefaciens dominated in the rumen of goats [21]. However, the abundances of R. bromii and F. succinogenes were different in different ruminant species.…”
Section: Discussionsupporting
confidence: 91%
“…Butyrivibrio (average relative abundance is 9.5% of total sequences) dominated in the stomach of sheep in the present study. The abundance of Butyrivibrio was in line with the previous report on the goat rumen microbiota, using cloned 16S rRNA gene analysis, where it accounted about 10.0% [21] and dairy cattle four stomach microbiota, using Illumina MiSeq (Department of Computer Science, North Arizona University, Flagstaff, AZ, USA) platform analysis, where Butyrivibrio accounted for about 5.1% [5]. Therefore, even if the different methods and different ruminant breeds were used, Butyrivibrio dominated the stomach of ruminants.…”
Section: Discussionsupporting
confidence: 89%
“…The population of this species was inhibited by ORO, but not by PEO at the similar dose level (Patra and Yu, 2014 ). Zhu et al ( 2014 ) also reported decreased 16S rRNA gene clones related to Butyrivibrio proteoclasticus and Pseudobutyribrio ruminis in the rumen of goats fed 0.8 g/d of GAO. In the present study, the ORO supplementation decreased the relative abundances of many OTUs of S. sucromutans , Lachnospiraceae incertae sedis , and unclassified Ruminococcaceae , but increased that of S. ruminis , and some members of Prevotella , and unclassified Bacteroidales , Lachnospiraceae , and Prevotellaceae .…”
Section: Discussionmentioning
confidence: 95%
“…Members of the genus Prevotella, numerically predominant in ruminants, are capable of utilizing starches, other noncellulosic polysaccharides, and simple sugars as energy sources (24). Members of the Butyrivibrio group (including the genera Butyrivibrio and Pseudobutyrivibrio) represented 12.98% of total bacteria in the rumina of goats (38) and were involved in the biohydrogenation of unsaturated C 18 fatty acids (39). Although some species of Campylobacter, such as Campylobacter concisus and other non-Campylobacter jejuni Campylobacter species, have been implicated in the initiation of gastrointestinal diseases (40), they represent persistent residents of rumen microbial communities (10).…”
Section: Figmentioning
confidence: 99%